2000 MPa grade low alloy, ultrahigh strength multiphase steels. (1st June 2013) - Hongyan, Li
Abstract : The benefit of steels with a combination of high strength and good ductility has attracted generations of researchers to work in this area. The strength of current Chinese structural steels typically falls in the range 400-1000 MPa. Higher strengths are desired to achieve the aims of saving energy and raw materials and protecting the environment, through reducing the weight of steel parts, or of improving safety standards. Thus, there is an urgent need to develop ultrahigh strength steel.